2017
DOI: 10.1158/1078-0432.ccr-16-2981
|View full text |Cite
|
Sign up to set email alerts
|

Successful Transfer of Umbilical Cord Blood CD34+ Hematopoietic Stem and Progenitor-derived NK Cells in Older Acute Myeloid Leukemia Patients

Abstract: Older acute myeloid leukemia (AML) patients have a poor prognosis; therefore, novel therapies are needed. Allogeneic natural killer (NK) cells have been adoptively transferred with promising clinical results. Here, we report the first-in-human study exploiting a unique scalable NK-cell product generated from CD34 hematopoietic stem and progenitor cells (HSPC) from partially HLA-matched umbilical cord blood units. Ten older AML patients in morphologic complete remission received an escalating HSPC-NK cell dose … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
124
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 155 publications
(128 citation statements)
references
References 44 publications
4
124
0
Order By: Relevance
“…Here, we used a feeder cell-free ex vivo system for the generation of human NK cells from cord blood HSCs (29). This system can generate therapeutic NK cells that have been proven to be safe in a phase I clinical trial (42). We have, furthermore, demonstrated that the NK cells formed using this system display the typical NK cell receptors, potent ADCC and produce IFN-γ similar to peripheral blood NK cells (28).…”
Section: Discussionmentioning
confidence: 99%
“…Here, we used a feeder cell-free ex vivo system for the generation of human NK cells from cord blood HSCs (29). This system can generate therapeutic NK cells that have been proven to be safe in a phase I clinical trial (42). We have, furthermore, demonstrated that the NK cells formed using this system display the typical NK cell receptors, potent ADCC and produce IFN-γ similar to peripheral blood NK cells (28).…”
Section: Discussionmentioning
confidence: 99%
“…UCB-NK-cell infusions were safe and well tolerated without signs of GvHD. Interestingly, UCB-NK cells expressing low levels of KIRs and CD16a at the end of the ex vivo culture, underwent further maturation post-transfer in vivo , resulting in the upregulation of KIRs and CD16a, but continued to preserve the activated phenotype denoted by high expression of NKp30, NKp44, NKp46, NKG2D, and DNAM (73). …”
Section: Adoptive Nk Cell Therapy In a Non-transplant Settingmentioning
confidence: 99%
“…In patients who have reached CR or morphologic CR, adoptive NK cell transfer can remarkably prolong disease-free progression. Of the 28 patients reported, 4 had CR lasting for about 1 year, 5 had CR lasting for about 1.5 years, and 10 had CR lasting for about 2 years [62][63][64]. Meanwhile, 24 out of 50 patients with active diseases reached CR [55,58,[65][66][67].…”
Section: Hematopoietic Malignanciesmentioning
confidence: 98%